ANALISIS DROP CALL DENGAN METODE LONG CALL DUAL MODE DI KOTA PONTIANAK - ., Hairurrahimin (Faculty of Engineering, Universitas Tanjungpura, 2017)
Drop Call is a broken connection when the communication is not desired by the user at the time of the call. Analysis of the cause of the drop call is done by Long Call Dual Mode method in Pontianak City, done by doing Drive Test by using Nemo Handy software. The test drive results recorded by Nemo Handy were analyzed using Nemo Analyzer software. Based on route taken at Jl. Jendral Ahmad Yani drop call occurred as much as 3 times, precisely at the location near the Kartini building, Jl. Sutoyo, and in front of the Pangsuma GOR with the results obtained both for data before and after handling. Specialized in Jl. Jendral Ahmad Yani, the cause of the drop call with the dual mode dual mode method is Missing Neighbours and the solution checks the parameters related to neighbour cells, creates new neighbors and removes the wrong neighbours. To route the CGM parade (Cap Go Meh) to Jl. Prince Antasari drop call occurs as much as 1 time caused by coverege problem related to problem coverege dead zone ie absence of CI (Cell Id) serving the area and handling solution that is done by adding new site at site Jl. Merapi. DCR (Drop Call Rate) The DCR (Drop Call Rate) result for both routes is 50%.) For both routes the value is 50%. Â Key words: Drop Call, Drive Test, Long Call Dual Mode, Missing Neighbour, Coverage Problem. Â